PENENTUAN BAHAN KERING BUAH SAWO SECARA TIDAK MERUSAK MENGGUNAKAN NIR SPECTROSCOPY - Suhandy, Diding (Teknologi Hasil Pertanian Fakultas Pertanian Universitas Lampung, 2008)
This work was conducted to develop a new measuring system for nondestructive dry matter prediction in sawo fruit using short wavelength near infrared (SW-NIR) spectroscopy. In this research, a number of 100 sawo fruits were used as samples. Spectra were acquired using a portable spectrometer (VIS-NIR USB4000, The Ocean Optics, USA) with 100 ms integration time and 50 scans for number of scanning. Dry matter was measured using oven drying. The calibration and validation model was developed using the partial least squares (PLS) regression method. The result showed that the best calibration model could be developed for original spectra in the wavelength range of 700-990 nm with F= 8, r = 0.92, SEC = 0.68 and SEP = 0.86. Keywords: Absorbance mode, dry matter, nondestructive method, sawo fruit, SW-NIR spectroscopy.